Impact of nanosilver-profenofos on cotton leafworm, Spodoptera littoralis (Boisd.) larvae - Ahmed, K.S. (2021)
In this work, the method is based on using silver nanoparticles (AgNPS) as a pesticide carrier by loading the organophosphorus pesticide profenofos on to their surface. The profenofos, AgNPS alone and nanocomposite profenofos (AgNPS@P) have been tested against second- and fourth-instar larvae of laboratory and field cotton leafworm. Our findings indicate that the AgNPS@P is more effective on cotton leafworm larvae than each of profenofos and nanosilver alone. The activity of AgNPS@P (LC50 = 0.94 and 5.15 ppm) was increased to 85 and 69 times more than that of profenofos (LC50 = 79.52 and 356.97 ppm) against second- and fourth-instar larvae of field cotton leafworm.